2018
DOI: 10.1016/j.ijcci.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A review on complementary natures of tangible user interfaces (TUIs) and early spatial learning

Abstract: Spatial skills are essential for everyday tasks, and technology blends seamlessly into children's everyday environment. Since spatiality as a term is ubiquitous in experience this paper bridges literature in two fields: theories on early spatial learning in cognitive development and potential benefits of tangible user interfaces (TUIs) for supporting very young children's spatial skills. Studies suggest that the period between 2 and 4 years of age is critical for training spatial skills (e.g., mental rotation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 50 publications
1
21
0
1
Order By: Relevance
“…Researcher Therefore, it is important to consider the tangible affordances of a physical representation of a voice agent for young children such that it can be part of physical play, including the use of physical props. This recommendation resonates with previous research findings suggesting that tangible interfaces were better at supporting children's active collaboration and more appropriate for younger children to refine their fine motor skills (Antle and Wise 2013, Baykal et al 2018, Horn et al 2012, Sylla et al 2016, Sylla et al 2015.…”
Section: Comparison With Screen-based Animated Agentsupporting
confidence: 84%
“…Researcher Therefore, it is important to consider the tangible affordances of a physical representation of a voice agent for young children such that it can be part of physical play, including the use of physical props. This recommendation resonates with previous research findings suggesting that tangible interfaces were better at supporting children's active collaboration and more appropriate for younger children to refine their fine motor skills (Antle and Wise 2013, Baykal et al 2018, Horn et al 2012, Sylla et al 2016, Sylla et al 2015.…”
Section: Comparison With Screen-based Animated Agentsupporting
confidence: 84%
“…Embodiment has become a paramount concept in HCI research (Dourish, 2001), and tangible interfaces have proven to be particularly well-suited for interaction design focusing on embodiment (Baykal et al, 2018). Specific to the present research, the benefits of tangible and embodied interaction have been observed in studies focused on a wide range of topics, including the relationship between spatial ability, puzzle solving, and abstract mapping (Macaranas et al, 2012;Antle and Wang, 2013); gaming performance (Reinhardt and Hurtienne, 2018); virtual reality interaction (Bozgeyikli and Bozgeyikli, 2019); and interactive learning environments (Malinverni et al, 2016).…”
Section: Related Workmentioning
confidence: 83%
“…The use of TUIs has been implemented in several learning applications, ranging from programming skills [33] to storytelling [34], science [35] as well as in the context of developmental disabilities [36], dyslexia [37], and visual impairment [38]. TUIs have also been proposed as optimal tools to enhance spatial learning in children, likely by improving mental rotation abilities [39]. The effectiveness of TUIs is grounded on the 'embodied' properties of such technological solutions, for example, studies show that gesturing about rotating objects improves mental rotation performance in children [40].…”
Section: Tangible User Interfacesmentioning
confidence: 99%